How Immigrant Parents and Local Parents Were Involved in Children's Education in Macau - Ng, Shun W.; Cheong, Ka W. (International Journal of Educational Reform, 2023)
The objective of this case study is to analyze how two groups of parents, a group who have newly arrived in Macau from Mainland China and the other who have resided in Macau for more than three decades, interact with the class teachers at the levels of ?two-way communication,? ?supervision of children at home,? and ?participating in decision making? in a secondary school. The findings will redound to the benefits of school leaders, teachers, and indirectly the parents in a sense that looking closely at the ethnic and cultural differences between parents can promote effective cooperation between parents and teachers.

Relationship between Student Teachers' Beliefs and Practices on Early Chinese Literacy Instruction - Sun, Chunrong; Ho, Ka Lee Carrie (Universal Journal of Educational Research, 2023)
This study explores the relationship between student teachers' beliefs and practices in early Chinese literacy instruction. Semi-structured interviews, classroom observation, and document analysis were conducted with six student teachers during their teaching practices. Findings indicated that the student teachers believed explicitly teaching literacy skills and imperceptible acquisition of literacy abilities through communication and meaning-making processes are essential in Chinese early literacy learning. However, they mainly taught Chinese literacy skills in their practices, which means the student teachers still needed to practice what they preached fully. The study suggests that possible reasons for the discrepancies include 'direct teaching' and 'rote learning' might be much easier for student teachers to design and conduct a lesson. Student teachers have limited abilities and experiences in conducting an ideal lesson, and the kindergarten curriculum and onsite supervisors highly influenced their teaching practices. The findings from this study suggested that more operational activities (such as designing lesson plans and conducting micro-teaching) should be used during pre-service training. Furthermore, the communication of educational beliefs between the university supervisor and the onsite supervisor should be strengthened.